Google trend and stock market: Does it matter? - Ratih Kusumawardhani; Risal Rinofah; Dandi Rukmana (Faculty of Economics and Business, University of Muhammadiyah Malang, 2021)
This study aims to determine the effect of the financial ratio and Google search volume (GSV) on stock returns of LQ-45 companies listed on the IDX for the 2015-2020 period. The study used purposive sampling and applied multiple linear regression analysis. The results showed that the Current Ratio (CR) and Return on Assets (ROA) insignificantly affect stock returns. Meanwhile, the Debt-to-Equity Ratio (DER) hurts stock returns significantly. This finding implies that signals from search data volume can help build profitable trading strategies.